A Proposed Java Static Slicing Approach - Basem Alokush; Mohammad Abdallah; Mustafa Alrifaee; Mosa Salah (Institute of Advanced Engineering and Science, 2018)
Program slicing is to abstract a part of source code depending on the point of interest. It used widely in maintenance, debugging and testing. There are many slicing techniques such as static, dynamic, and amorphous. In this paper, we choose to develop a new approach applying static slicing on Java programs. The new approach simplifies the data dependency using arrays. A new Tool called Java Multi-Slicing Tool (JavaMST) has been introduced to apply this approach.JavaMST presents new ways to slice any simple java code segment, it allows you to extract the variables and its direct and indirect dependencies from the code, using backward, forward or both slicing techniques to produce the needed code. This tool is a simple tool designed to deal with simple java code segments. JavaMST can be run under any operating system and does not require a specialized platforms or plug-ins. Therefore, it is useful to be used for educational purposes.